239 PATIENT PERCEPTIONS OF THE EDITH (EMERGENCY DEPARTMENT IN THE HOME) SERVICE. (25th October 2022) - Davis, AJ; Kenny, L; Delaney, A; Doyle, C; Sweeney, A; Nally, SM; Namara, RM
Abstract: Background: The EDITH service provides an alternative to Emergency Department (ED) attendance for the older adult by providing emergency care in the person home. It is imperative to explore how this service is received by the key stakeholders in order to ensure it is meeting the needs of older adults and to improve and diversify same. Methods: A patient feedback survey was circulated to patients and family members who received the EDITH service. A postal option and a QR code leading to an online option were utilised. 50 surveys were randomly selected for inclusion. Quantitative data was analysed via paper count method and thematic analysis was completed for the qualitative data. Results: 74% rated the service as "excellent", 22% "very good" and 4% "good". Alternative options to the service were identified as "going to ED" 22%, "going to GP" 22%, "waited until they would get better" 4%, "waited until they got worse" 2%, "would do nothing" 6%. 80% rated the combined expertise of a doctor and OT as "extremely important", 94% rated the home visit aspect as "extremely important" and 90% rated ED avoidance as "extremely important". Key themes that emerged regarding what the service does well included "personalised care", "ED avoidance", "compassion" and "timeliness of service". Areas for improvement included "improving communication loop to both patients and/or community services! and "ability to directly access the service". 95% of respondents advised they would or have already recommended the service to others. Of note, a key theme in the comments section was the need for a similar service in other hospitals. Conclusion: The EDITH service appears to be meeting stake-holders expectations, areas for improvement have been identified and are currently being addressed. It is imperative to obtain the perception of the service user and to tailor interventions accordingly, this feedback is invaluable in order to meet future service needs.